Achieving porous tungsten with high porosity by selective dissolution of W-Fe alloy. (June 2021) - Ge, Shuai; Zhang, Jian; Xu, Zhigang; Luo, Guoqiang; Shen, Qiang
Abstract: Porous W with high porosity of 75.7 % was achieved by selective dissolution using Fe as active elements. The results showed that W-Fe pseudo alloy precursor was sintered at 800°C, the nano C powder helped in-situ formation of the W6 Fe6 C phase and the interface of W-W and W-Fe were both combined by W6 Fe6 C. It enabled the precursor to inherit the morphology of the green compacts without deformation. W-W connection remained and formed W framework after the selective dissolution of Fe. With the increasing of heat treatment temperature, the porosity decreased and the compressive strength increased, the change of the pore size is very little due to the effect of the W6 Fe6 C in the W framework. Graphical abstract: Image, graphical abstract